Autonomous Energy Supply System of a Mobile Home Based on Pyrolysis and Biogas Devices - Rakhmatov, A. (International Journal on Orange Technologies, 2023)
This article is devoted to the analysis of the application of loading energy with integrated pyrolysis and biogas devices in a mobile home with an energy supply system based on alternative energy sources. Thermal technical parameters of pyrolysis and biogas devices required for energy supply of a mobile home with an average volume of 40 m3, heat balance equations and heat-technical sources of energy supply of this mobile home based on alternative energy sources.